Actual and Perceived Emotional Similarity in Couples' Daily Lives. Issue 2 (March 2020) - Sels, Laura; Ruan, Yan; Kuppens, Peter; Ceulemans, Eva; Reis, Harry
We used two experience sampling studies to examine whether close romantic partners' feelings of love and perceived partner responsiveness are better predicted by their actual emotional similarity or by their perceived emotional similarity. Study 1 revealed that the more partners were emotionally similar, the more they perceived their partner as responsive. This effect was mediated by perceived similarity, indicating that emotional similarity had to be detected in order to exert an effect. Further, when people overperceived their emotional similarities, they also reported more perceived partner responsiveness. Study 2 replicated these findings, by revealing similar effects for actual and perceived similarity on the love people reported to feel toward their partner. Implications for understanding the factors that predict feelings of love and responsiveness in close relationships are discussed.